Status of Informed Consent in Surgical Patients in Hospitals of Sindh Pakistan - Tariq Abdullah, Muhammad Akbar, Shahnawaz Khatti, Ishrat Rahim Katyar, Karim Bux, Muhammad Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Informed consent (IC) is a critical step in ensuring that patients understand implications of their treatment decisions. Materials and Methods: It is observational cross-sectional study. Non probability purposive sampling was used to collect data from different surgical units. Adult postsurgical patients were questioned using a standardized questionnaire between the first- and fifth-day following surgery in two general hospitals in Sindh province (Hyderabad and Jamshoro). Data was analyzed using SPSS and Microsoft excel. Results: A total of 78% of individuals who claimed to have read it found informed consent to be easy to understand. Less than half of patients thought information brought them some emotional solace, while 23.2% of patients reported feeling more anxious after hearing information. This study suggests enhancing the process of obtaining consent forms by including additional information and avenues for discussion on written documents rather than relying solely on verbal communication. Conclusion: Patients under age of sixty and patients who had completed more schooling tended to read written informed consent forms more frequently. Orally communicated pre-operative information suited patients’ requirements better than written informed consent. Surgeon needs to get informed permission from patient and inform them about operation type, potential consequences and other treatment options. Keywords: Informed consent, Medical Ethics, Surgery, Hospital, Surgeons, Health, Sindh.